Development of a novel parallel soft manipulator with sensing capabilities. (1st January 2023) - Xiang, Chaoqun; Li, Zhiwei; Guo, Haoyu; Yun, Tao; Jiang, Haosheng; Guan, Yisheng
Abstract: It is challenging to equip a soft manipulator with sensors without compromising its mechanical properties. In this paper, we explain the design, analysis, and building of an innovative, low-cost soft parallel manipulator with sensing and actuation capabilities. Innovative bubble artificial muscle actuators serve as the connecting rod and contraction type actuator for the manipulator, as well as an opto-mechanical tactile sensor (TacTip) for objects detection. We propose a simulation method for the key structural design parameters of TacTip, and the influence of TacTip's pin height, pin diameter, and surrounding pin angle on perceptual sensing has been examined via testing, which can provide a design guideline for the TacTip's the structure. The impact of the counterweight on the soft parallel manipulator end-ascending effector's and descending velocity, as well as its vertical and horizontal workspace, has been the topic of dynamic tests using a range of counterweights. The soft parallel manipulator's workspace has been analyzed. In addition, an innovative, cost-effective, and simple soft-smart parallel robotic manipulator (PSM) control system has been built, and a demonstration of the detection and movement of the soft parallel manipulator is shown. The results demonstrate that the soft parallel manipulator described in this research is capable of detecting motion and collisions. It is anticipated that this soft-smart PSM would expand the employment of optical tactile sensors and artificial muscle actuators in material handling and size/shape sorting assembly lines.